PEMBERDAYAAN UMAT MELALUI BANK SHARIA’H - Marjudo, Abd. Basyir (Hunafa: Jurnal Studia Islamika, 2008)
One of the Indonesian Muslims’ attempts to empower the Islamic society in the aspect of economy is to establish Islamic bank.  The purpose of this bank is to enhance the prosperity of the Islamic society who does not wish to use conventional banks employing interest system. The reason is that bank interest, according to them, is identical to riba. Therefore, they avoid using conventional banks employing  interest system, and use Islamic banks, instead.Kata Kunci : pemberdayaan ekonomi, bank shar’iah,